The impact of visual elements on Kula cakes packaging design / Nor Fazlyn Zulkefly - Zulkefly, Nor Fazlyn (2022)
This study is proposed because it aims to the impact of visual elements design on kula cakes packaging upon consumer buying behavior. It studied the impact of visual elements on kula cakes packaging because packaging is one of the maximum essential and effective factors, which affects consumers’ buy decisions. A study was conducted to determine the relationship between packaging features and customer buying behavior to determine the impact of visual aspects of packaging on consumers. This study is going deeper into the institution of visual elements on food packaging (kula cakes packaging) to research their capacity to draw attention. Packaging elements as visual elements have been the subject of many contemporary studies. The elements tested in the study were: illustration, graphics, color, and elements of the package. On the contrary, illustration, graphics, colors, and elements of the package had a significant impact on the choices. Participants preferred illustration over photography, concrete pattern over abstract and vivid colors over dull. These results can be used as guidelines in marketing and design. The research model was built and tested to show the impact of visual and verbal package features on consumer purchase decisions, taking into account that a package can be viewed as a collection of distinct aspects expressing different messages to a consumer. In this study, we used a survey to gather information on visual elements design (graphic design, color, and illustration), user impression (attention, purchase, and repurchase), and personal experience (emotions evoked and useful benefits). When it comes to packaging responses, there is a distinction between professional rank and age involvement. The data also imply that different features of package design are associated with varied benefits.